Peningkatan Motivasi Belajar Melalui Pendekatan Contextual Teaching And Learning (Ctl) pada Pembelajaran Bahasa Indonesia - Muliarni Muliarni (Indonesian Institute for Counseling, Education and Therapy (IICET), 2016)
The aim of this research to know about (1) implementation of Contextual Teaching And Learning (CTL) Approach can improve student’s learning At the IX.6 grade in learening motivation Indonesian SMPN 1 Nan Sabaris Padang Pariaman District. Contextual Teaching And Learning (CTL) can increas student’s spirit and response in solving problems set by the teacher, by increasing ability of communication and student learning outcomes obtained. Such as: (a) increased student collaboration and mutual help among students to solve problems in the learning process (b) increasing the compactness between students (c) the increased involvement of students in the learning process. (2) Contextual learning, has given a new feel in learning Indonesian so that learning is more effective. This is proven by the existence of significant changes to the completeness of student learning. By using contextual approach teachers find out innovate and create in the eye easy. Its approach can efficient and effective time to achieve the goal of learning and thinking effectively in solving simple problems.